Undifferentiated embryonal sarcoma of the liver treated with associating liver partition and portal vein ligation for staged hepatectomy in a young adult: A case report. (2020) - Schepelew, Dmitri; Reese, Tim; Horling, Katja; Frenzel, Christian; Oldhafer, Karl J.
Highlights: First Case Report about ALPPS for the treatment of an undifferentiated embryonal sarcoma of the Liver. The feasibility of the ALPPS procedure in a newly faced tumor-entity. Importance of an intraoperative histological evaluation of the parenchyma to estimate the individual risk for liver failure. Abstract: Introduction: Embryonal sarcomas of the liver (ESL) are extremely rare solid tumors appearing mainly in children. The therapeutic standard for an ESL is a margin free resection combined with chemotherapy. The Associating Liver Partition and Portal Vein Ligation for Staged Hepatectomy (ALPPS) procedure as a surgical therapy offers a curative approach for liver tumors of various origins where the future liver remnant (FLR) would be insufficient after a one-staged (extended) hemihepatectomy. Presentation of Case: A 19-year-old patient was diagnosed with an undifferentiated embryonal sarcoma of the liver (UESL) in the right liver lobe with oligometastatic spread to the lungs. After neoadjuvant chemotherapy remission was enough to plan a resection of the liver tumor. During the operation we changed our strategy from one-stage hepatectomy to ALPPS because of borderline FLR and macroscopic and histologic liver damage to avoid posthepatectomy liver failure. The interstage and postoperative course of the patient was uneventful beside postoperative bile leakage, which was treated by interventional drainage and stenting. Discussion: The ALPPS-procedure as a comparatively new surgery was considered over a portal vein ligation or embolization. ALPPS shows a faster hypertrophy compared to standard one-staged hemihepatectomy with decreased or similar proliferation, apoptosis or angiogenesis (at least for CRLM) Conclusion: In experienced centers the ALPPS-procedure is evolving as the safer approach in hemihepatectomys where the FLR is critical. Additionally, ALPPS can serve as an intraoperative option when liver volume and quality seem not to be sufficient and is to be considered when facing new tumor-entities.